Contemporary methods of treatment of colorectal cancer - Kozłowska, Monika; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2015)
Today, colorectal cancer (CRC) is the third most frequently diagnosed worldwide malignant cancer in males, and the second in females, with more than 1,200,000 new cases and more than 600,000 deaths, annually. Screening tests in oncology allow the detection of cancerous disease at an early, asymptomatic stage. The procedures most frequently performed in the case of colorectal cancer include: low anterior resection by the Dixon method (manual suture or staplers); abdominoperineal resection of the rectum by the Miles method; surgical procedure by the Hartmann method; local resection. Various techniques of preoperative radiotherapy are applied, aimed at tumour mass reduction (scheme I) and/or obtaining local sterilisation (schemes I and II), which results in the reduction of local metastases (by approximately 50%), as well as an improvement with respect to long-term survival (by approximately 10%). At present, the following drugs for treatment of various forms of colorectal cancer have been registered by the Food and Drug Administration (FDA): fluorouracil capecitabine irinotecan, oxaliplatin, cetuximab, and bevacizumab. The combination of complete cytoreductive surgery (CCS), the goal of which is the removal of all visible (macroscopically) cancer foci, with a simultaneous intraperitoneal chemotherapy in hyperthermia – HIPEC, destroying microscopic remains of the disease, allows the curing of some patients with peritoneal cancer. The effect of the action of monoclonal antibodies – cetuximab and panitumumab – is the inhibition of proliferation of cancer cells, intensification of their apoptosis, as well as reduction of synthesis and secretion of pro-angiogenic factors, such as interleukin 8 (IL-8) and vascular endothelial growth factor. In addition, antibodies targeted against EGFR impair the repair of DNA damage caused by chemotherapy and radiotherapy in the cells of the malignant tumour.